Practical implementation issues and challenges for biobanks in the return of individual research results - Bledsoe, M.; Grizzle, W.; Clark, B.; Zeps, Nikolajs (2012)
Whether or not to give research results back to individuals whose specimens are used for biomedical research is a subject of considerable controversy. Much of the debate has been focused around the ethical and legal concerns with some consideration of broader social issues such as whether or not people will be affected by such information for employment or health care. Much less attention has been paid to biobanks that collect the specimens used to generate the research findings and the issues and operational requirements for implementing return of individual research results. In this article, we give the biobanks’ perspective and highlight that given the diversity among the types of biobanks, it may be difficult to design and implement a blanket policy in this complex area. We discuss the variability in the types of biobanks and some important issues that should be considered in determining whether or not research results should be provided to individuals whose specimens are used in biomedical research. We also discuss challenges that should be considered in implementing any approaches to the return of research results.